A genetic association study reveals the relationship between the oral microbiome and anxiety and depression symptoms - Li, Chun'e; Chen, Yujing; Wen, Yan; Jia, Yumeng; Cheng, Shiqiang; Liu, Li; Zhang, Huijie; Pan, Chuyu; Zhang, Jingxi; Zhang, Zhen; Yang, Xuena; Meng, Peilin; et al. (Frontiers in Psychiatry, 2022)
Background. Growing evidence supports that the alterations in the gut microbiota play an important role in the etiology of anxiety, depression, and other psychiatric disorders. The potential effect of oral microbiota on mental health has received little attention. Methods. Using the latest genome-wide association study (GWAS) summary data of the oral microbiome, polygenic risk scores (PRSs) of 285 salivary microbiomes and 309 tongue dorsum microbiomes were conducted. Logistic and linear regression models were applied to evaluate the associations of salivary-tongue dorsum microbiome interactions with anxiety and depression. Two-sample Mendelian randomization (MR) was utilized to compute the causal effects between the oral microbiome, anxiety, and depression. Results. We observed significant salivary-tongue dorsum microbiome interactions related to anxiety and depression traits. Significantly, 1 common interaction was observed to be associated with both anxiety score and depression score, Centipeda periodontii SGB 224 × Granulicatella uSGB 3289 (P depression score = 1.41×10-8, P anxiety score = 5.10×10-8). Furthermore, we detected the causal effects between oral microbiome and anxiety and depression. Importantly, we identified 1 salivary microbiome associated with both anxiety and depression in both the UKB database and Finngen public database, Eggerthia (P IVW-major depression-UKB = 2.99×10-6, P IVW-Self-reported anxiety/panic attacks-UKB = 3.06×10-59, P IVW-depression-Finngen = 3.16×10-16, P IVW-anxiety-Finngen = 1.14×10-115). Conclusion. This study systematically explored the relationships between the oral microbiome and anxiety and depression, which could help improve our understanding of disease pathogenesis and propose new diagnostic targets and early intervention strategies.